A kind of anti-scratch and anti-collision TPU color-changing film and preparation method thereof
By using a hot pressing process of carbon nanofiber reinforcement layer and weather-resistant color layer in the TPU color-changing film, combined with cellulose triacetate surface layer and water-repellent oil-repellent finishing agent, the problem of insufficient scratch-proof and collision-proof effect of the existing TPU color-changing film is solved, and higher weather resistance and service life are achieved, and construction is simplified.
Patent Information
- Application Number
- CN202310710456.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-15
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-06-15
AI Technical Summary
The existing TPU color-changing film has weak protection effect in terms of scratch resistance and collision resistance, and has a short service life, which has insufficient weather resistance and construction simplicity.
The hot pressing process of the TPU base layer, strength layer and weather-resistant color layer reinforced by carbon nanofiber is adopted, combined with cellulose triacetate as the surface material, and a water-repellent oil-repellent finishing agent is applied to the surface to form a scratch-proof and collision-resistant TPU color-repellent film.
It significantly improves the rigidity, ductility and weather resistance of the color-changing film, extends the service life, enhances the protection effect on the automotive paint surface, and simplifies the construction process.
Smart Images

Figure BDA0004287463860000061 
Figure BDA0004287463860000071
Abstract
Description
Technical Field
[0001] The invention relates to the field of TPU films, and in particular to an anti-scratch and anti-collision TPU color-changing film and a preparation method thereof. Background Art
[0002] During the use of a car, it will inevitably be eroded by objects such as wind, sun, acid rain, sea water, chewing gum, bird droppings, and insect corpses. The gravel and snow-melting agent hit by the wheels will cause irreversible damage to the paint surface. The paint surface will lose its luster in light cases, and turn yellow, cracked and scarred in severe cases. The car will be damaged and suffer.
[0003] Invisible car film is a thermoplastic polyurethane film (TPU) containing UV-resistant polymers, anti-yellowing, super toughness, wear resistance, no yellowing, easy to stick, anti-collision and scratch resistance. After installation, it can isolate the car paint from the air, prevent acid rain, oxidation, scratches, and protect the paint surface for a long time. However, the existing car films all use memory repair function for scratch and collision protection. That is, when scratched or abraded by general external forces, the coating can be simply heated by a hot air blower and restored to its original state in a few minutes. It does not improve the scratch and collision resistance effect through mechanical resistance such as strength and toughness, and the protection of metal car bodies is still weak. Summary of the invention
[0004] Purpose of the invention: The technical problem to be solved by the present invention is to provide a scratch-resistant and anti-collision TPU color-changing film and a preparation method thereof in view of the deficiencies in the prior art. The scratch-resistant and anti-collision TPU color-changing film has a long service life, strong scratch-resistant and anti-collision ability, high brightness, strong stain resistance and impact resistance, good weather resistance, and simple construction.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a scratch-resistant and collision-resistant TPU color-changing film comprises the following steps:
[0007] S1: dissolving thermoplastic polyurethane elastomer in dimethylformamide, adding carbon nanofibers and mixing thoroughly, and electrospinning on a release film to obtain a release-base layer;
[0008] S2: fully mixing the polyaromatic amide with TiO2 nanoparticles, Al2O3 nanoparticles, SiC nanoparticles, and SiO2 nanoparticles, and then melt-electrospinning on the release-base layer prepared in step S1 to obtain a release-base-strength layer;
[0009] S3: dissolving polymethyl methacrylate and polyvinylidene fluoride together in a DMAc / acetone mixed solution, adding inorganic pigment nanoparticles, and electrospinning on the release-base-strength layer prepared in step S2 to obtain a release-base-strength layer-weather-resistant color layer;
[0010] S4: Coat the surface of release-base-strength layer-weather-resistant color layer with water-repellent and oil-repellent finishing agent solution, and then coat the surface with 1,4-dioxane solution containing cellulose triacetate after hot pressing and vacuum drying to obtain the product.
[0011] Specifically, in step (1), the usage ratio of the thermoplastic polyurethane elastomer, dimethylformamide and carbon nanofiber is (15-19) g:100 ml:(0.5-0.8) g; the outer diameter of the carbon nanofiber is 50-600 nm.
[0012] Specifically, in step (1), the electrospinning parameters are voltage 15-25 kV, receiving distance 12-20 cm, flow rate 1.5-2.0 ml / h; the thickness of the obtained release-substrate layer is 40-80 μm.
[0013] Specifically, in step (2), the usage ratio of the polyaromatic amide, TiO2 nanoparticles, Al2O3 nanoparticles, SiC nanoparticles, and SiO2 nanoparticles is 100g:(1-3)g:(30-40)g:(5-10)g:(20-25)g; the particle sizes of the TiO2 nanoparticles, Al2O3 nanoparticles, SiC nanoparticles, and SiO2 nanoparticles are 20-50nm, 300-500nm, 100-200nm, and 100-200nm, respectively.
[0014] Specifically, in step (2), the polyaromatic amide is fully mixed with TiO2 nanoparticles, Al2O3 nanoparticles, SiC nanoparticles, and SiO2 nanoparticles and then melted at 250-270°C, and then melt-electrospun on the release-substrate layer. The melt-electrospinning parameters are as follows: a spinning solution temperature of 270-300°C, a voltage of 12-20 kV, a receiving distance of 12-15 cm, and a flow rate of 1.0-1.5 ml / h; the thickness of the resulting release-substrate-strength layer is 300-600 μm.
[0015] Specifically, in step (3), the usage ratio of polymethyl methacrylate, polyvinylidene fluoride, DMAc / acetone mixed solution, and inorganic pigment nanoparticles is (8-10) g:(2-4) g:100 ml:(0.3-0.5) g; the volume ratio of the DMAc / acetone mixed solution is 6:4; and the particle size of the inorganic pigment nanoparticles is 50-100 nm.
[0016] Specifically, in step (3), the electrospinning parameters are voltage 15-18 kV, receiving distance 20-22 cm, flow rate 0.5-0.8 ml / h, and the thickness of the obtained release-base-strength layer-weather-resistant color layer is 800-1000 μm.
[0017] Specifically, in step (4), the water-repellent and oil-repellent finishing agent is selected from any one of EG-616G, EG-660 or EG-652G, and the concentration of the water-repellent and oil-repellent finishing agent solution is 5-15% w / v; the concentration of the 1,4-dioxane solution containing cellulose triacetate is 5-12% w / v.
[0018] Specifically, in step (4), the hot pressing molding parameters are hot pressing for 3 minutes at 120-170°C and 1000-1500N; and the vacuum drying temperature is 60-80°C.
[0019] Furthermore, the anti-scratch and anti-collision TPU color-changing film prepared by the above preparation method is also within the protection scope of the present invention.
[0020] Beneficial effects:
[0021] (1) The present invention uses a hot pressing process of the carbon nanofiber-reinforced TPU base layer, strength layer and weather-resistant color layer to make the TPU base layer and weather-resistant color layer penetrate into the strength layer, causing the stress of the strength layer to be enhanced, and the rigidity and ductility of the color-changing film to be greatly enhanced.
[0022] (2) The present invention uses cellulose triacetate as the surface layer of the color-changing film, which can enhance the glossiness of the color-changing film and has a certain hygroscopicity, so that the surface is not easy to accumulate charges, so it is not easy to absorb dust in the air, and the surface is smoother, and it also has the memory repair function of the car cover. In addition, the use of a water-repellent and oil-repellent finishing agent under the cellulose triacetate layer is also to prevent the cellulose triacetate surface from absorbing moisture and penetrating downward to affect the base-strength layer-weather-resistant color layer. DETAILED DESCRIPTION
[0023] The present invention can be better understood with reference to the following examples.
[0024] Example 1
[0025] S1. 18 g of thermoplastic polyurethane elastomer was dissolved in 100 ml of dimethylformamide, 0.7 g of carbon nanofibers with an outer diameter of 300 nm was added and mixed thoroughly, and electrospun on a release film at a voltage of 20 kV, a receiving distance of 15 cm, and a flow rate of 1.7 ml / h to obtain a 75 μm thick release-base layer;
[0026] S2. 100 g of polyaromatic amide was thoroughly mixed with 2 g of TiO2 nanoparticles with a particle size of 28 nm, 36 g of Al2O3 nanoparticles with a particle size of 420 nm, 8 g of SiC nanoparticles with a particle size of 120 nm, and 24 g of SiO2 nanoparticles with a particle size of 140 nm, melted at 260° C., and melt-electrospun on the release-substrate layer prepared in step S1, with a spinning solution temperature of 280° C., a voltage of 18 kV, a receiving distance of 14 cm, and a flow rate of 1.2 ml / h to obtain a 580 μm thick release-substrate-strength layer;
[0027] S3. 9 g of polymethyl methacrylate and 3 g of polyvinylidene fluoride were dissolved in 100 ml of a DMAc / acetone solution with a volume ratio of 6:4, 0.4 g of inorganic pigment nanoparticles with a particle size of 80 nm were added, and electrospun on the release-substrate-strength layer prepared in step S2 at a voltage of 17 kV, a receiving distance of 21 cm, and a flow rate of 0.7 ml / h to obtain a 950 μm thick release-substrate-strength layer-weather-resistant color layer;
[0028] S4. Remove the release-base-strength layer-weather-resistant color layer from the electrospinning collector, coat the surface with 12% w / v water- and oil-repellent finishing agent EG-660 solution, hot press at 150°C and 1200N for 3 minutes, then coat the surface with 8% w / v cellulose triacetate 1,4-dioxane solution, and vacuum dry at 70°C to obtain a scratch- and collision-resistant TPU color-changing film.
[0029] Example 2
[0030] S1. 15 g of thermoplastic polyurethane elastomer was dissolved in 100 ml of dimethylformamide, 0.5 g of carbon nanofibers with an outer diameter of 50 nm were added and mixed thoroughly, and electrospun on a release film at a voltage of 15 kV, a receiving distance of 12 cm, and a flow rate of 1.5 ml / h to obtain a 40 μm thick release-base layer;
[0031] S2. 100 g of polyaromatic amide was thoroughly mixed with 1 g of TiO2 nanoparticles with a particle size of 20 nm, 30 g of Al2O3 nanoparticles with a particle size of 300 nm, 5 g of SiC nanoparticles with a particle size of 100 nm, and 20 g of SiO2 nanoparticles with a particle size of 100 nm, melted at 250° C., and melt-electrospinned on the release-substrate layer prepared in step S1, with a spinning solution temperature of 270° C., a voltage of 12 kV, a receiving distance of 12 cm, and a flow rate of 1.0 ml / h to obtain a 300 μm thick release-substrate-strength layer;
[0032] S3. 8 g of polymethyl methacrylate and 2 g of polyvinylidene fluoride were dissolved in 100 ml of a DMAc / acetone solution with a volume ratio of 6:4, 0.3 g of inorganic pigment nanoparticles with a particle size of 50 nm were added, and electrospun on the release-substrate-strength layer prepared in step S2 at a voltage of 15 kV, a receiving distance of 20 cm, and a flow rate of 0.5 ml / h to obtain a release-substrate-strength layer-weather-resistant color layer with a thickness of 800 μm;
[0033] S4. Remove the release-base-strength layer-weather-resistant color layer from the electrospinning collector, coat the surface with 5% w / v water- and oil-repellent finishing agent EG-616G solution, hot press at 120°C and 1000N for 3 min, then coat the surface with 5% w / v cellulose triacetate 1,4-dioxane solution, and vacuum dry at 60°C to obtain a scratch- and collision-resistant TPU color-changing film.
[0034] Example 3
[0035] S1. 19 g of thermoplastic polyurethane elastomer was dissolved in 100 ml of dimethylformamide, 0.8 g of carbon nanofibers with an outer diameter of 600 nm was added and mixed thoroughly, and electrospun on a release film at a voltage of 25 kV, a receiving distance of 20 cm, and a flow rate of 2.0 ml / h to obtain a release-base layer of 80 μm thick;
[0036] S2. 100 g of polyaromatic amide was thoroughly mixed with 3 g of TiO2 nanoparticles with a particle size of 50 nm, 40 g of Al2O3 nanoparticles with a particle size of 500 nm, 10 g of SiC nanoparticles with a particle size of 200 nm, and 25 g of SiO2 nanoparticles with a particle size of 200 nm, melted at 270° C., and melt-electrospun on the release-substrate layer prepared in step S1, with a spinning solution temperature of 300° C., a voltage of 20 kV, a receiving distance of 15 cm, and a flow rate of 1.5 ml / h to obtain a 600 μm thick release-substrate-strength layer;
[0037] S3. 10 g of polymethyl methacrylate and 4 g of polyvinylidene fluoride were dissolved in 100 ml of a DMAc / acetone solution with a volume ratio of 6:4, 0.5 g of inorganic pigment nanoparticles with a particle size of 100 nm were added, and electrospun on the release-substrate-strength layer prepared in step S2 at a voltage of 18 kV, a receiving distance of 22 cm, and a flow rate of 0.8 ml / h to obtain a 1000 μm thick release-substrate-strength layer-weather-resistant color layer;
[0038] S4. Remove the release-base-strength layer-weather-resistant color layer from the electrospinning collector, coat the surface with 15% w / v water- and oil-repellent finishing agent EG-652G solution, hot press at 170°C and 1500N for 3 minutes, then coat the surface with 12% w / v cellulose triacetate 1,4-dioxane solution, and vacuum dry at 80°C to obtain a scratch- and collision-resistant TPU color-changing film.
[0039] Comparative Example 1 (without strengthening layer)
[0040] S1. 18 g of thermoplastic polyurethane elastomer was dissolved in 100 ml of dimethylformamide, 0.7 g of carbon nanofibers with an outer diameter of 300 nm was added and mixed thoroughly, and electrospun on a release film at a voltage of 20 kV, a receiving distance of 15 cm, and a flow rate of 1.7 ml / h to obtain a 75 μm thick release-base layer;
[0041] S2. 9 g of polymethyl methacrylate and 3 g of polyvinylidene fluoride were dissolved in 100 ml of a DMAc / acetone solution with a volume ratio of 6:4, 0.4 g of inorganic pigment nanoparticles with a particle size of 80 nm were added, and electrospun on the release-substrate layer prepared in step S1 at a voltage of 17 kV, a receiving distance of 21 cm, and a flow rate of 0.7 ml / h to obtain a 950 μm thick release-substrate-weather-resistant color layer;
[0042] S3. Remove the release-base-weather-resistant color layer from the electrospinning collector, coat the surface with 12% w / v water- and oil-repellent finishing agent EG-660 solution, hot press at 150°C and 1200N for 3 minutes, then coat the surface with 8% w / v cellulose triacetate 1,4-dioxane solution, and vacuum dry at 70°C to obtain a TPU color-changing film.
[0043] Comparative Example 2 (without hot pressing process)
[0044] S1. 18 g of thermoplastic polyurethane elastomer was dissolved in 100 ml of dimethylformamide, 0.7 g of carbon nanofibers with an outer diameter of 300 nm was added and mixed thoroughly, and electrospun on a release film at a voltage of 20 kV, a receiving distance of 15 cm, and a flow rate of 1.7 ml / h to obtain a 75 μm thick release-base layer;
[0045] S2. 100 g of polyaromatic amide was thoroughly mixed with 2 g of TiO2 nanoparticles with a particle size of 28 nm, 36 g of Al2O3 nanoparticles with a particle size of 420 nm, 8 g of SiC nanoparticles with a particle size of 120 nm, and 24 g of SiO2 nanoparticles with a particle size of 140 nm, melted at 260° C., and melt-electrospun on the release-substrate layer prepared in step S1, with a spinning solution temperature of 280° C., a voltage of 18 kV, a receiving distance of 14 cm, and a flow rate of 1.2 ml / h to obtain a 580 μm thick release-substrate-strength layer;
[0046] S3. 9 g of polymethyl methacrylate and 3 g of polyvinylidene fluoride were dissolved in 100 ml of a DMAc / acetone solution with a volume ratio of 6:4, 0.4 g of inorganic pigment nanoparticles with a particle size of 80 nm were added, and electrospun on the release-substrate-strength layer prepared in step S2 at a voltage of 17 kV, a receiving distance of 21 cm, and a flow rate of 0.7 ml / h to obtain a 950 μm thick release-substrate-strength layer-weather-resistant color layer;
[0047] S4. Remove the release-base-strength layer-weather-resistant color layer from the electrospinning collector, coat the surface with 12% w / v water- and oil-repellent finishing agent EG-660 solution, dry at 150°C for 3 minutes, then coat the surface with 8% w / v cellulose triacetate 1,4-dioxane solution, and vacuum dry at 70°C to obtain a TPU color-changing film.
[0048] Comparative Example 3 (without water and oil repellent finishing)
[0049] S1. 18 g of thermoplastic polyurethane elastomer was dissolved in 100 ml of dimethylformamide, 0.7 g of carbon nanofibers with an outer diameter of 300 nm was added and mixed thoroughly, and electrospun on a release film at a voltage of 20 kV, a receiving distance of 15 cm, and a flow rate of 1.7 ml / h to obtain a 75 μm thick release-base layer;
[0050] S2. 100 g of polyaromatic amide was thoroughly mixed with 2 g of TiO2 nanoparticles with a particle size of 28 nm, 36 g of Al2O3 nanoparticles with a particle size of 420 nm, 8 g of SiC nanoparticles with a particle size of 120 nm, and 24 g of SiO2 nanoparticles with a particle size of 140 nm, melted at 260° C., and melt-electrospun on the release-substrate layer prepared in step S1, with a spinning solution temperature of 280° C., a voltage of 18 kV, a receiving distance of 14 cm, and a flow rate of 1.2 ml / h to obtain a 580 μm thick release-substrate-strength layer;
[0051] S3. 9 g of polymethyl methacrylate and 3 g of polyvinylidene fluoride were dissolved in 100 ml of a DMAc / acetone solution with a volume ratio of 6:4, 0.4 g of inorganic pigment nanoparticles with a particle size of 80 nm were added, and electrospun on the release-substrate-strength layer prepared in step S2 at a voltage of 17 kV, a receiving distance of 21 cm, and a flow rate of 0.7 ml / h to obtain a 950 μm thick release-substrate-strength layer-weather-resistant color layer;
[0052] S4. Remove the release-base-strength layer-weather-resistant color layer from the electrospinning collector, hot-press at 150°C and 1200N for 3 minutes, then apply 8% w / v cellulose triacetate 1,4-dioxane solution to the surface, and vacuum dry at 70°C to obtain a TPU color-changing film.
[0053] Test on the effect of rain erosion on the hardness of color-changing film
[0054] The color-changing film samples of Examples 1-3 and Comparative Examples 1-3 were treated under standard conditions using ASTM G73-10 "Standard Test Method for Liquid Impact Erosion Using a Rotating Apparatus", and then the hardness of the film was measured according to ASTM D2240 "Standard Test Method for Shore Hardness of Rubber Properties". The results are shown in Table 1.
[0055] Table 1
[0056]
[0057] From the results in Table 1, it can be seen that the TPU color-changing film prepared in the embodiment of the present invention has a relatively high hardness, indicating that it has good mechanical strength and good protective effect, and after rain erosion, the hardness is maintained well. However, the TPU color-changing film of Example 1 does not have a reinforcement layer, which greatly affects its basic mechanical strength; the TPU color-changing film of Example 2 does not use a hot pressing process, and the base layer, strength layer and weather-resistant color layer are separated into three layers. Due to the short-board effect, the hardness of the base layer and the weather-resistant color layer is not as good as the hardness layer, so the hardness is low; the TPU color-changing film of Example 3 is not water- and oil-repellent, resulting in the downward movement of water vapor after rain erosion, which destroys the composite structure of the base layer-strength layer-weather-resistant color layer, and has a greater impact on the hardness.
[0058] Mechanical properties determination
[0059] The color-changing film samples of Examples 1-3 and Comparative Examples 1-3 were treated under standard conditions using ASTM G73-10 "Standard Test Method for Liquid Impact Erosion Using a Rotating Apparatus", and then the mechanical properties were measured. The results are shown in Table 2.
[0060] Table 2
[0061]
[0062] From the results in Table 2, it can be seen that the color-changing film of the embodiment of the present invention shows good tensile strength and ductility after rain erosion. However, Comparative Example 1 has no strengthening layer, poor basic strength, and poor ductility. Comparative Example 2 does not use a hot pressing process, and the interlayer peeling strength is low, resulting in poor mechanical properties. Comparative Example 3 does not undergo water- and oil-repellent finishing, resulting in water vapor going down after rain erosion, destroying the composite structure of the base layer-strength layer-weather-resistant color layer, which has a greater impact on tensile strength and ductility.
[0063] The present invention provides a method and idea for a scratch-proof and anti-collision TPU color-changing film and a method for preparing the same. There are many methods and approaches to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention. All components not specified in this embodiment can be implemented using existing technologies.
Claims
1. A method for preparing a scratch-resistant and collision-resistant TPU color-changing film, characterized in that: The steps include: S1: dissolving thermoplastic polyurethane elastomer in dimethylformamide, adding carbon nanofibers and mixing thoroughly, and electrospinning on a release film to obtain a release-base layer; S2: fully mixing the polyaromatic amide with TiO2 nanoparticles, Al2O3 nanoparticles, SiC nanoparticles, and SiO2 nanoparticles, and then melt-electrospinning on the release-base layer prepared in step S1 to obtain a release-base-strength layer; S3: dissolving polymethyl methacrylate and polyvinylidene fluoride together in a DMAc / acetone mixed solution, adding inorganic pigment nanoparticles, and electrospinning on the release-base-strength layer prepared in step S2 to obtain a release-base-strength layer-weather-resistant color layer; S4: coating a water-repellent and oil-repellent finishing agent solution on the surface of the release-base-strength layer-weather-resistant color layer, hot pressing and forming, and then coating a 1,4-dioxane solution containing cellulose triacetate on the surface, and vacuum drying to obtain; In step S1, the usage ratio of the thermoplastic polyurethane elastomer, dimethylformamide and carbon nanofiber is (15-19) g:100 ml:(0.5-0.8) g; The electrospinning parameters are voltage 15-25 kV, receiving distance 12-20 cm, flow rate 1.5-2.0 ml / h; In step S2, the polyaromatic amide is fully mixed with TiO2 nanoparticles, Al2O3 nanoparticles, SiC nanoparticles, and SiO2 nanoparticles, and then melted at 250-270°C, and then melt-electrospun on the release-substrate layer. The melt-electrospinning parameters are as follows: a spinning solution temperature of 270-300°C, a voltage of 12-20 kV, a receiving distance of 12-15 cm, and a flow rate of 1.0-1.5 ml / h; In step S3, the usage ratio of polymethyl methacrylate, polyvinylidene fluoride, DMAc / acetone mixed solution, and inorganic pigment nanoparticles is (8-10) g:(2-4) g:100 ml:(0.3-0.5) g; the volume ratio of the DMAc / acetone mixed solution is 6:4; the particle size of the inorganic pigment nanoparticles is 50-100 nm; The electrospinning parameters are voltage 15-18 kV, receiving distance 20-22 cm, and flow rate 0.5-0.8 ml / h.
2. The method for preparing the anti-scratch and anti-collision TPU color-changing film according to claim 1, characterized in that: In step S1, the outer diameter of the carbon nanofiber is 50-600 nm.
3. The method for preparing the anti-scratch and anti-collision TPU color-changing film according to claim 1, characterized in that: In step S1, the thickness of the obtained release-base layer is 40-80 μm.
4. The method for preparing the anti-scratch and anti-collision TPU color-changing film according to claim 1, characterized in that: In step S2, the usage ratio of the polyaromatic amide, TiO2 nanoparticles, Al2O3 nanoparticles, SiC nanoparticles, and SiO2 nanoparticles is 100g:(1-3)g:(30-40)g:(5-10)g:(20-25)g; the particle sizes of the TiO2 nanoparticles, Al2O3 nanoparticles, SiC nanoparticles, and SiO2 nanoparticles are 20-50nm, 300-500nm, 100-200nm, and 100-200nm, respectively.
5. The method for preparing the anti-scratch and anti-collision TPU color-changing film according to claim 1, characterized in that: In step S2, the thickness of the obtained release-base-strength layer is 300-600 μm.
6. The method for preparing the anti-scratch and anti-collision TPU color-changing film according to claim 1, characterized in that: In step S3, the thickness of the obtained release-base-strength layer-weather-resistant color layer is 800-1000 μm.
7. The method for preparing the anti-scratch and anti-collision TPU color-changing film according to claim 1, characterized in that: In step S4, the water-repellent and oil-repellent finishing agent is selected from any one of EG-616G, EG-660 or EG-652G, and the concentration of the water-repellent and oil-repellent finishing agent solution is 5-15% w / v; the concentration of the 1,4-dioxane solution containing cellulose triacetate is 5-12% w / v.
8. The method for preparing the anti-scratch and anti-collision TPU color-changing film according to claim 1, characterized in that: In step S4, the hot pressing molding parameters are hot pressing for 3 minutes at 120-170°C and 1000-1500N; and the vacuum drying temperature is 60-80°C.
9. The anti-scratch and anti-collision TPU color-changing film prepared by the preparation method described in any one of claims 1 to 8.
Citation Information
Patent Citations
Green casting level automobile film and preparation method thereof
CN106553407A
Highly-waterproof highly-breathable nanofiber membrane and preparation method thereof
CN110258021A